2020
DOI: 10.2174/1874210602014010019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chitosan Nanoparticle as A Final Irrigation Solution on The Smear Layer Removal, Micro-hardness and Surface Roughness of Root Canal Dentin

Abstract: Background: Root canal irrigation is one of the most important stages during root canal treatment. One of the requirements of root canal irrigation material is that it can eradicate the smear layer but does not alter the physical properties of the root canal dentin. Objective: To investigate the effect of chitosan nanoparticle as a final irrigation solution on the smear layer removal, micro-hardness and surface roughness of root canal dentin. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…According to research, the final treatment with 0.2% CS nanoparticles (CNPs) had a similar influence on eliminating the smear layer as 17% EDTA; nevertheless, 0.2% CNP produced more microhardness and minor surface roughness over dentin than 17% EDTA. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…According to research, the final treatment with 0.2% CS nanoparticles (CNPs) had a similar influence on eliminating the smear layer as 17% EDTA; nevertheless, 0.2% CNP produced more microhardness and minor surface roughness over dentin than 17% EDTA. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Ethylenediaminetetraacetic acid (EDTA) is often used in the clinic and as the gold standard for final irrigation solution since its ability to chelate with calcium ions in dentin, thus dissolving the inorganic component from smear layers [10]. However, the prolonged application time of EDTA to the dentinal wall can cause dentin erosion and reduce microhardness [11]. Besides, EDTA has no antibacterial properties and a pollutant [12].…”
Section: Introductionmentioning
confidence: 99%
“…Apple vinegar was selected in this study for its advantages as it possesses; chelating capacity, antibacterial action, biocompatibility, costeffectiveness, and possible anti-inflammatory role (30) . Moreover, it was found that a 3-minute contact time of 5 ml 17% EDTA irrigation solution is effective in smear layer removal (24,25) .…”
Section: Discussionmentioning
confidence: 99%
“…Using NaOCl alternating with 17% EDTA irrigation can help in root canal disinfection and smear layer removal (6,7) . On the other hand, EDTA solution has some drawbacks as it can harm the periapical tissue and cause dentinal erosions (8,9) .…”
Section: Introductionmentioning
confidence: 99%